Efficacy of non-invasive brain stimulation for post-stroke depression: a systematic review and meta-analysis - Peizhang Huang; Haojie Wang; Cheng Huang; Changjie Mei; Linrong Liao; Yakun Li (Frontiers in Psychology, 2026)
Objective Post-stroke depression (PSD) is a common neuropsychiatric complication after stroke and is associated with poorer functional recovery and quality of life. This systematic review and meta-analysis evaluated the efficacy and safety of non-invasive brain stimulation (NIBS), specifically repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS), for PSD. Methods PubMed, Embase, Web of Science, the Cochrane Library, and Scopus were searched from inception to April 2025. Randomized controlled trials comparing rTMS or tDCS with sham stimulation, placebo, usual care, or other control interventions in adults with PSD were eligible. Standardized mean differences (SMDs) with 95% confidence intervals (CIs) were calculated for depressive symptoms and secondary outcomes. Fixed- or random-effects models were selected according to heterogeneity. Results Seventeen randomized controlled trials involving 917 participants were included. Compared with control interventions, NIBS was associated with a greater reduction in depressive symptoms (SMD = −1.24, 95% CI: −1.74 to −0.73, p < 0.001). Subgroup analyses showed significant effects for both rTMS (SMD = −1.06, 95% CI: −1.59 to −0.52) and tDCS (SMD = −1.94, 95% CI: −3.25 to −0.63), although the difference between modalities was not statistically significant. High-frequency rTMS showed a numerically larger effect than low-frequency rTMS, but the subgroup difference was not significant. NIBS was also associated with improvements in activities of daily living (SMD = 0.80) and quality of life (SMD = 0.83). No serious stimulation-related adverse events were reported. Conclusion Current randomized evidence suggests that rTMS and tDCS may improve depressive symptoms in patients with PSD and appear generally well tolerated. However, the certainty of these findings is limited by substantial heterogeneity, small sample sizes in several trials, and variation in stimulation protocols. Further well-designed trials are needed to define optimal stimulation parameters, treatment timing, and long-term clinical effects.